2014
DOI: 10.1002/chem.201402833
|View full text |Cite
|
Sign up to set email alerts
|

Detoxifying Polyhalogenated Catechols through a Copper‐Chelating Agent by Forming Stable and Redox‐Inactive Hydrogen‐Bonded Complexes with an Unusual Perpendicular Structure

Abstract: The use of selective metal chelating agents with preference for binding of a specific metal ion to investigate its biological role is becoming increasingly common. We found recently that a well-known copper-specific chelator 2,9-dimethyl-1,10-phenanthroline (2,9-Me 2 OP) could completely inhibit the synergistic toxicity induced by tetrachlorocatechol (TCC) and sodium azide (NaN 3 ). However, its underlying molecular mechanism is still not clear. Here, we show that the protection by 2,9-Me 2 OP is not due to it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The crystal network of some molecular complexes contains solvent molecules. As follows from the literature review 49 co‐crystals or solvated QUE co‐crystals have been studied so far [11,12,19–34] . In the described co‐crystal structures, quercetin and co‐former are linked by the hydrogen bonds of different types: O−H…N, O−H…O, N−H…O, O−H…S, N−H + …O − (Table S1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The crystal network of some molecular complexes contains solvent molecules. As follows from the literature review 49 co‐crystals or solvated QUE co‐crystals have been studied so far [11,12,19–34] . In the described co‐crystal structures, quercetin and co‐former are linked by the hydrogen bonds of different types: O−H…N, O−H…O, N−H…O, O−H…S, N−H + …O − (Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…[18] Intensive research on co-crystallization of QUE with various organic co-formers has been carried out to improve its physicochemical properties and pharmacokinetic profiles. [11,12,[19][20][21][22][23][24][25][26][27][28][29][30][31] The molecules of the co-formers contained amino, carbonyl, carboxyl, amide or heterocyclic groups (with nitrogen or sulphur atoms). The crystal network of some molecular complexes contains solvent molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During our systematic studies on synergism of biochemical and toxicological interactions between organic environmetal pollutants (especially chlorophenols and their quinoid metabolites) and inorganic compounds (especially redox-active transition metals such as copper and iron, and H 2 O 2 ), we found that reactive hydroxyl/alkoxyl radicals can be produced by XQs and hydroperoxides through the novel pathway independent of transition-metal ions, which was proposed through a new-type nucleophilic substitution followed by homolytical decomposition reaction mechanism , (Scheme ). Intriguingly, except for the traditional hydroxyl/alkoxyl radicals, several unprecedented carbon-centered quinone ketoxy radicals and oxygen-centered quinone-enoxy radicals were also measured and identified from the XQs/hydropeoxide system. , …”
Section: Introductionmentioning
confidence: 99%